The Russian food, alcohol, and tobacco consumption patterns during transition - Marian Rizov; Thomas Herzfeld; Sonya K. Huffman (Collegium Antropologicum (Coll Antropol), 2012)
The paper presents evidence on the impact of individual characteristics as well as regional macroeconomic factors on changes in fat, protein, alcohol and tobacco consumption, and on diet's diversity during the transition period 1994 - 2004 in Russia. The results from estimating first difference demand functions using Russian Longitudinal Monitoring Survey (RLMS) data suggest that individual characteristics such as initial consumption patterns, gender, education, household income, and access to a garden plot all have a significant impact on the consumption behaviour. Regarding the macroeconomic variables, inflation has a significant impact on alcohol and tobacco consumption, while unemployment significantly impacts only smoking behaviour. Russian consumers respond to own prices of fat and protein as well as to own prices of alcohol and tobacco but to a lesser extent. Analysis of subsamples based on different initial consumption patterns reveals significant heterogeneity in consumption responses.
Keywords: D12; I12; I15; R11; 330; food; alcohol; cigarettes; consumption; transition; Russia